Phase composition, size, orientation, and antenna effects of self-assembled anodized titania nanotube arrays; a polarized micro-raman investigation - V. Likodimos; Stergiopoulos, T.; P. Falaras; Kunze, J.; Schmuki, P. (Journal of Physical Chemistry C, 2008)
Polarized micro-Raman spectroscopy was applied to investigate the phase composition and transformation from the amorphous to the crystalline state, size effects, and the crystallographic orientation and antenna polarization effects on self-organized anodic TiO2 nanotubes (NTs), The morphological characteristics of the NTs were tailored by electrochemical anodization in both aqueous (phosphate buffer) and organic (ethylene glycol) electrolytes as well as in perchlorate/chloride-containing electrolytes. Postgrowth thermal annealing was confirmed to reduce markedly the organic and inorganic species encapsulated in the as-grown arrays and drive the transformation of the amorphous titania to nanocrystalline anatase. Crystallite size and shape effects as well as oxygen nonstoichiometry were investigated through the variation of the low-frequency Eg anatase mode for the TiO2 NT arrays produced in different electrolyte media, and the results were compared with the predictions of the phonon confinement model for anatase nanoparticles. Polarized micro-Raman spectra identify partial orientation effects, indicating preferential (101) growth in the case of the shorter TiO2 NTs (length ≤ 1 μm), while a predominant random orientation of the anatase crystallites is found for the long tubes (length ≥ 10 μm). Polarized measurements on the cross section of free-standing NT membranes revealed significant enhancement of the Raman intensity when the polarization of the incident laser beam is parallel to the NT axis, indicating an "antenna" effect attributed to the enhanced light scattering along the cylindrical NT structure. Such an effect could result in optimum optical properties and selectively enhanced vectorial transport of electric carriers. © 2008 American Chemical Society.
cited By 101